Exploring accounting control for cash revenue and disbursement in micro enterprises - Nur'aini Rokhmania; Nurul Hasanah Uswati Dewi; Pepie Diptyana (Universitas Hayam Wuruk Perbanas, 2020)
This study aims to describe the implementation of accounting procedures and internal control in micro enterprises. The research data were obtained from source persons consisting of micro business owners 'LBB Surabaya' and 'Travel Pahlawan', employees, and customers. The data were analysed using a descriptive qualitative. The results showed that the accounting records maintained were Cash Books that were matched with bank records. There have been no written accounting procedures and reconciliation between company’s cash records and bank books. Internal control was implemented in the form of good communication and values in holding trust. However, it is necessary to carry out reconciliation, transaction documentation and document archiving well and minimize cash transactions to reduce the risk of fraud and increase the accuracy of accounting data.